Alginate-based Microcapsules for Cell Therapy: A Combination of Techniques Designed to Characterize their Stiffness and Surface Properties - Paz, Laura; Virumbrales, María; Ciriza, Jesús; Alcaine, Clara; Espona, Albert; Doblaré, Manuel; Sáenz del Burgo, Laura; Ziani, Kaoutar; Pedraz, José Luis; Fernández, Luis; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2020)
Cell encapsulation in hydrogel-based microspheres has demonstrated successes in regenerative cell therapy. We developed a workflow based on Atomic Force Microscopy (AFM) and a microfluidic constriction system to characterize stiffness and surface properties of microcapsules.